2020
DOI: 10.3389/fmed.2020.00097
|View full text |Cite
|
Sign up to set email alerts
|

A Standard Lipid Panel Is Insufficient for the Care of a Patient on a High-Fat, Low-Carbohydrate Ketogenic Diet

Abstract: High-fat, low-carbohydrate ketogenic diets have recently become popular for weight loss and the treatment of numerous chronic diseases; however, the general medical community still expresses concern regarding the impact of high-fat diets on serum lipids and cardiovascular risk. Herein, we report on a young man who adopted a ketogenic diet to treat his inflammatory bowel disease. Incidentally, changes in his serum lipids that would be considered adverse by current standards were noted. A more critical analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
1
17
0
1
Order By: Relevance
“…HDL, low-density lipoprotein (LDL) and triglycerides were all within normal limits at 54 mg/dL, 129 mg/dL and 97 mg/dL, respectively [ 35 ]. It has been suggested that a standard lipid panel may not be sufficient to analyze the effect of KDTs on cardiovascular disease (CVD) [ 83 ]. Subfractions of HDL and LDL vary by particle size and density and have been proposed as a measure to improve assessment of CVD risk [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…HDL, low-density lipoprotein (LDL) and triglycerides were all within normal limits at 54 mg/dL, 129 mg/dL and 97 mg/dL, respectively [ 35 ]. It has been suggested that a standard lipid panel may not be sufficient to analyze the effect of KDTs on cardiovascular disease (CVD) [ 83 ]. Subfractions of HDL and LDL vary by particle size and density and have been proposed as a measure to improve assessment of CVD risk [ 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, greater LDL-cholesterol levels associated with a KD during weight loss has been previously reported [ 52 ]. However, lipid profile changes raised by KD may need a deeper analysis, considering also lipid sub-fractionations [ 53 ]. Therefore, large-scale, long-term intervention trials with comparative arms are needed to prove safety and efficacy of KD in NAFLD.…”
Section: Nutritional Management Of Nafldmentioning
confidence: 99%
“…A more recently published case study on a young man who used a Mediterranean KD diet for treating his IBS had some interesting findings [ 120 ]. The doctors looked at more detailed lipid subfractions to determine the lipid outcomes of cardiovascular risk, which was unique.…”
Section: The Effect Of the Ketogenic Diet On Lipidology And Cardiovascular Riskmentioning
confidence: 99%